A Randomized Control Trial of a Peer Adherence and Nutritional Support Program for Public Sector Antiretroviral Patients - Booysen, Frederik; de Walque, Damien; Over, Mead; Hashimoto, Satoko; de Reuck, Chantell (World Bank, Washington, DC, 2016)
Access to antiretroviral treatment has expanded rapidly in South Africa, making it the country in the world with the largest treatment program. As antiretroviral treatment coverage continues to rise in resource-constrained settings, effective community-based adherence support interventions are of central importance in ensuring the long-term sustainability of treatment. This paper reports the findings from a randomized control trial of a peer adherence and nutritional support program implemented in a public health care setting in South Africa's antiretroviral treatment program. The analysis assesses the impact of these peer adherence and nutritional support interventions on self-reported adherence, timeliness of clinic and hospital visits, and immunologic response to antiretroviral treatment. Peer adherence and nutritional support improved the timeliness of adults´ clinic and hospital visits for routine follow-up while on antiretroviral treatment. Peer adherence support impacted positively on immunologic response to antiretroviral treatment. Scale-up of effective and sustainable community-based, peer-driven adherence and nutritional support interventions should form part of the United Nations AIDS Treatment 2.0 strategy's community mobilization and health system strengthening pillar.